Elemental Status of Pregnant and Lactating Women in Bassa L.G.A of Plateau State, Nigeria - Madukosiri, C.H.; Adoga, G.I. (Pakistan Journal of Nutrition, 2011)
The present study has determined the serum levels of ten elements (sodium, potassium, magnesium, calcium, zinc, copper, iron, manganese, phosphorus and chloride) in the three trimesters of pregnancy and in lactation. Four hundred and thirty two apparently healthy pregnant, lactating and non-pregnant/non-lactating (control) women participated in the study. Atomic absorption spectrophotometric method was used for the analysis of some of the elements. The determination of inorganic phosphate was carried out by phosphomolybdic acid method, while the level of chloride was measured by the mercuric nitrate method. Our results showed that the serum sodium levels in pregnancy were significantly higher than the levels obtained in their control counterpart and in lactation (p